Transport and development: synthesis and next steps? - Banister, D; Givoni, M; Bonilla, D; Hickman, R (Edward Elgar Publishing, 2015)
The relationships between transport and development have become a central part of transport thinking, particularly in the cities of the developed countries. These cities already have a high level of connectivity with dense street patterns, roads and public transport systems that can accommodate most traffic under normal conditions. The quality of that transport network has been seen to be central to the economic success of cities and in making them an attractive centre for investment. Increasingly, the transport benefits of new infrastructure investment have been enhanced by the wider economic benefits brought about through agglomeration economies, labour market benefits (better employment opportunities), and other multiplier effects. In the rapidly growing cities in the developing world, there is still the need for new infrastructure to accommodate the huge increases in demand arising from population growth and from increased wealth. Yet in time, even these ‘new cities’ will have to limit new investment as demand for travel always seems to exceed the means to provide for that demand. Questions are now being raised in all cities about what is a sufficient amount of infrastructure and whether issues of demand management and capacity management should become the central concerns of decision makers rather than continuing to follow the supply led future.